1998
DOI: 10.1177/088307389801301204
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Structure and Function in Sturge-Weber Syndrome: Evidence of Neurologic and Radiologic Progression

Abstract: Sturge-Weber syndrome is characterized by the presence of a port-wine nevus, epilepsy, stroke-like episodes, headache, and developmental delay. We studied 20 cases to test the hypothesis that decreased cerebral blood flow alters neurologic function by affecting cellular glucose metabolism. Group A consisted of 10 patients with a mean age of 1.75 years and early seizure onset (6.8 months), whereas group B was composed of older patients (mean age, 15.3 years) with later onset of seizures (3.7 years). Neurologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 29 publications
1
73
1
1
Order By: Relevance
“…Blood flow in SWS was previously investigated using nuclear medicine techniques such as PET and SPECT (10,21,22). While PWI may be less quantitative than PET, it does offer advantages in that it enables functional assessment in the same study that provides superior morphological characterization, does not require ionizing radiation, and is able to differentiate venous vs. arterial causes of hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood flow in SWS was previously investigated using nuclear medicine techniques such as PET and SPECT (10,21,22). While PWI may be less quantitative than PET, it does offer advantages in that it enables functional assessment in the same study that provides superior morphological characterization, does not require ionizing radiation, and is able to differentiate venous vs. arterial causes of hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In several cases, perfusion (single-photon emission computed tomography (SPECT) imaging) and metabolism (using [ 18 F] fluorodeoxyglucose SPECT) abnormalities were evident before structural abnormalities developed (9), which suggests that functional measures may be more sensitive for early diagnosis of the disease. Furthermore, Maria and colleagues (10) demonstrated that reductions in perfusion and glucose metabolism in a longitudinal study of several young patients corresponded to their neurological deterioration.…”
mentioning
confidence: 97%
“…Aggressive treatment of epilepsy is advo- cated, 12 with some studies even suggesting neurodevelopmental benefits with prophylactic anticonvulsants before the onset of seizures. 13 Prophylactic daily aspirin 14 and early surgery when seizures are not controlled by medical treatment may also be of benefit. 12 SWS has a spectrum of clinical and imaging findings, and it is important to recognize those patients at the fringes of the spectrum who may benefit from therapies and monitoring applied in more conventional cases.…”
Section: Discussionmentioning
confidence: 99%
“…This capillary dysplasia may occur on other parts of the body. Calcium deposits frequently occur within the abnormal leptomeningeal capillaries and these can be associated with seizures and delayed development [48]. Whole genome sequencing of paired affected and unaffected patient samples disclosed a unique arginine and glutamine mutation in GNAQ in 88% of affected samples from patients [49].…”
Section: Sturge-weber Syndromementioning
confidence: 99%